2008
DOI: 10.1016/j.physd.2007.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional Euler equations: Where do we stand?

Abstract: The three-dimensional Euler equations have stood for a quarter of a millenium as a challenge to mathematicians and physicists. While much has been discovered, the nature of solutions is still largely a mystery. This paper surveys some of the issues, such as singularity formation, that have cost so much effort in the last 25 years. In this light we review the Beale-Kato-Majda theorem and its consequences and then list some of the results of numerical experiments that have been attempted. A different line of end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
191
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(197 citation statements)
references
References 104 publications
6
191
0
Order By: Relevance
“…These results were based on earlier work by McIntyre and Roulstone, and were reviewed by them in McIntyre & Roulstone (2002). It has also been shown that the three-dimensional Euler equations has a quaternionic structure in the dependent variables (Gibbon 2002) and that this idea can be used to discuss the evolution of orthonormal frames on particle trajectories: see Gibbon et al (2006), Gibbon (2007Gibbon ( , 2008a and Gibbon & Holm (2007). The use of different sets of dependent and independent variables in geophysical models of cyclones and fronts has facilitated some remarkable simplifications of otherwise hopelessly difficult nonlinear problems: see Hoskins & Bretherton (1972).…”
Section: Equations For An Incompressible Fluidmentioning
confidence: 99%
“…These results were based on earlier work by McIntyre and Roulstone, and were reviewed by them in McIntyre & Roulstone (2002). It has also been shown that the three-dimensional Euler equations has a quaternionic structure in the dependent variables (Gibbon 2002) and that this idea can be used to discuss the evolution of orthonormal frames on particle trajectories: see Gibbon et al (2006), Gibbon (2007Gibbon ( , 2008a and Gibbon & Holm (2007). The use of different sets of dependent and independent variables in geophysical models of cyclones and fronts has facilitated some remarkable simplifications of otherwise hopelessly difficult nonlinear problems: see Hoskins & Bretherton (1972).…”
Section: Equations For An Incompressible Fluidmentioning
confidence: 99%
“…The 3D Euler equations have a rich mathematical theory, for which the interested readers may consult the excellent surveys [2,18,24] and the references therein. This paper primarily concerns the existence or nonexistence of globally regular solutions to the 3D Euler equations, which is regarded as one of the most fundamental yet most challenging problems in mathematical fluid dynamics.…”
Section: Introduction the Celebrated Three-dimensional (3d) Incomprementioning
confidence: 99%
“…Other interesting pieces of work are [10,47], which studied axisymmetric Euler flows with complex initial data and reported singularities in the complex plane. A more comprehensive list of interesting numerical results can be found in the review article [24].…”
Section: Introduction the Celebrated Three-dimensional (3d) Incomprementioning
confidence: 99%
“…Standing open for more than 250 y and closely related to the Clay Millennium Prize Problem on the Navier-Stokes equations, the problem has received great attention from not only the mathematics but also the physics and engineering communities, where the formation of singularities in inviscid (Euler) flows is believed to be relevant to the creation of small scales in viscous turbulent flows (1)(2)(3). The finite-time blowup problem has been studied extensively from both mathematical and numerical points of view.…”
mentioning
confidence: 99%